The nature and genesis of solution cavities (Makondos) in Transvaal Cave breccias - Brink, A. B. A.; Partridge, T. C. (Bernard Price Institute for Palaeontological Research, 1980)
The discovery of a large part of the cranium of a hominid, evidently closely related to Homo habilis (Hughes and Tobias 1977) in a solution cavity within the calcified Member 5 of the Sterkfontein Formation (Partridge 1978) has again drawn attention to the frequent occurrence of these features in the hominid-bearing breccias of the Transvaal. The authors first studied these features at Makapansgat (fig. 1) some fifteen years ago and have since then become aware of their very widespread occurrence in soluble rocks in many parts of the world. All subsequent information has served to confirm the origin of these features, but, since these were never published, it is worthwhile to place these findings on record. Solution cavities, or Makondos, in the Transvaal cave breccias are soil-filled pits shaped like an inverted cone. Their walls and intervening areas of the calcified cave deposit are usually rough, and the coalescing of adjacent cavities below the surface is common. They seldom exceed 2 m in diameter and 6 m in depth and occur at intervals of 2 to 3 m in the calcified cave deposit.
Main article
Keywords: solution cavities; Transvaal; cave breccias